Planning of distributed generation sources wind and PV in IEEE 33-bus system - Krar Shakir Alibrahimi; Seyed Mohamed Hassan Hossaini (ITEGAM-JETIA, 2025)
To mitigate the impacts of rising power consumption and new technologies for distributed generation, microgrids are being developed. Another consequence of this is the expansion of the distribution network to include more microgrids, often known as multi-microgrid systems.